2020
DOI: 10.18016/ksutarimdoga.vi.723544
|View full text |Cite
|
Sign up to set email alerts
|

Tıbbi Bitkilerden Elde Edilen Uçucu Yağların Kimyasal Bileşimi ve Gal Oluşturan Bitki Patojeni Bakteriyel Hastalık Etmenlerine Karşı Antibakteriyel Etkinlikleri

Abstract: The aims of this study were to determine chemical composition of essential oils from different plant species and their antibacterial activities against gal-forming plant pathogenic bacterial disease agents Rhizobium radiobacter, Pseudomonas savastanoi pv. savastanoi and P.savastanoi pv. nerii. The chemical compositions of essential oils were identified by GC/MS. The major constituents of the essential oils were carvacrol in Thymbra spicata var. spicata (66.88%) and Origanum syriacum (79.8%), thymol in Thymus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The literature reports supported these findings concerning other medicinal plants. Indeed, several studies have reported the chemical composition of LSEO, with some indicating that, in addition to the fenchone/camphor chemotypes, the chemical compositions of LSEO collected in Morocco and Greece contained 1,8-cineole and camphene, and α-cardinol, respectively, while others disclosed the presence of myrtenyl acetate, bornyl acetate, linalyl acetate, camphene, linalool, borneol, γ-terpinene, lavandulyl acetate, and caryophyllene as major compounds [ 10 , 18 , 43 , 44 , 45 , 46 ]. Besides the presence of some main compounds, our study clearly revealed the chemical composition quantitative and qualitative variability of L. stoechas plants collected from three different regions.…”
Section: Resultsmentioning
confidence: 99%
“…The literature reports supported these findings concerning other medicinal plants. Indeed, several studies have reported the chemical composition of LSEO, with some indicating that, in addition to the fenchone/camphor chemotypes, the chemical compositions of LSEO collected in Morocco and Greece contained 1,8-cineole and camphene, and α-cardinol, respectively, while others disclosed the presence of myrtenyl acetate, bornyl acetate, linalyl acetate, camphene, linalool, borneol, γ-terpinene, lavandulyl acetate, and caryophyllene as major compounds [ 10 , 18 , 43 , 44 , 45 , 46 ]. Besides the presence of some main compounds, our study clearly revealed the chemical composition quantitative and qualitative variability of L. stoechas plants collected from three different regions.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal and antibacterial effects of essential oils against fungi and bacteria that infect both humans and plants have been demonstrated by many studies. Additionally, new studies have revealed the antiphytoviral activities of essential oils against plant viruses, even though numerous studies have already shown their antiviral activities against viruses that infect humans and animals (Kalemba and Kunicka, 2003;Bozkurt et al, 2020;Ma and Yao, 2020;Wani et al, 2021;Parikh et al, 2021;Taglienti et al, 2022). There is not any study that discusses the docking technique of essential oils against plant viruses, despite the fact that several studies in the scientific literature demonstrate the antiviral potential of essential oils against viruses that infect humans using an in silico docking approach.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…on the stems Although all applications were found to be successful in suppressing the speck disease symptoms on the leaves and stem, Turf-Set, ISR-2000 and Sergomil applications were determined to be the most successful applications. In many studies, the antimicrobial activities of essential oils and nanoparticles have been also investigated against many plant pathogenic bacteria and it has been reported that they have high efficacies (Bozkurt et al, 2020;Şahin et al, 2021;Soylu et al, 2022;Şahin et al, 2022). Reduced phosphorus (P) compounds containing phosphite (Phi) have been investigated since the 1930s as potential sources to meet P requirements (MacIntire et.…”
Section: Introductionmentioning
confidence: 99%